Design and development of 99mTc-labeled FAPI tracers for SPECT imaging and 188Re therapy - Lindner, Thomas; Altmann, Annette; Krämer, Susanne; Kleist, Christian; Loktev, Anastasia; Kratochwil, Clemens; Giesel, Frederik L.; Mier, Walter; Marmé, Frederik; Debus, Jürgen; Haberkorn, Uwe (Journal of nuclear medicine, 2020)
Most epithelial tumors recruit fibroblasts and other nonmalignant cells and activate them into cancer-associated fibroblasts. This often leads to overexpression of the membrane serine protease fibroblast-activating protein (FAP). It has already been shown that DOTA-bearing FAP inhibitors (FAPIs) generate high-contrast images with PET/CT scans. Since SPECT is a lower-cost and more widely available alternative to PET, 99mTc-labeled FAPIs represent attractive tracers for imaging applications in a larger number of patients. Furthermore, the chemically homologous nuclide 188Re is available from generators, which allows FAP-targeted endoradiotherapy. Methods: For the preparation of 99mTc-tricarbonyl complexes, a chelator was selected whose carboxylic acids can easily be converted into various derivatives in the finished product, enabling a platform strategy based on the original tracer. The obtained 99mTc complexes were investigated in vitro by binding and competition experiments on FAP-transfected HT-1080 (HT-1080-FAP) or on mouse FAP-expressing (HEK-muFAP) and CD26-expressing (HEKCD26) HEK cells and characterized by planar scintigraphy and organ distribution studies in tumor-bearing mice. Furthermore, a first-in-humans application was done on 2 patients with ovarian and pancreatic cancer, respectively. Results: 99mTc-FAPI-19 showed specific binding to recombinant FAP-expressing cells with high affinity. Unfortunately, liver accumulation, biliary excretion, and no tumor uptake were observed on planar scintigraphy for a HT-1080-FAP-xenotransplanted mouse. To improve the pharmacokinetic properties, hydrophilic amino acids were attached to the chelator moiety of the compound. The resulting 99mTc-labeled FAPI tracers revealed excellent binding properties (≤45% binding; >95% internalization), high affinity (half-maximal inhibitory concentration, 6.4-12.7 nM), and significant tumor uptake (≤5.4% injected dose per gram of tissue) in biodistribution studies. The lead candidate 99mTc-FAPI-34 was applied for diagnostic scintigraphy and SPECT of patients with metastasized ovarian and pancreatic cancer for follow-up to therapy with 90Y-FAPI-46. 99mTc-FAPI-34 accumulated in the tumor lesions, as also shown on PET/CT imaging using 68Ga-FAPI-46. Conclusion: 99mTc-FAPI-34 represents a powerful tracer for diagnostic scintigraphy, especially when PET imaging is not available. Additionally, the chelator used in this compound allows labeling with the therapeutic nuclide 188Re, which is planned for the near future.
Im Titel sind "99m" und "188" hochgestellt
Gesehen am 26.11.2020